Integrais de Riemann em sólidos de revolução com uso do software Geogebra - MIRANDA, Renan Augusto da Silva (2022)
This work addresses some reﬂections and discussions on Riemann integrals for the calculation of volumes and how to use GeoGebra as an auxiliary tool for this purpose. IS shown how to use the simple integral (with only one variable) for volume calculations of solids, especially solids of revolution as well as GeoGebra is also shown as 3D visualization tool for these solids. The objective is to portray the characteristic of the object in study without showing strong interest in the possible applications and beneﬁts resulting from the research in the educational area, being therefore a qualitative basic research.